2021
DOI: 10.1097/mco.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Purine metabolites and complex diseases: role of genes and nutrients

Abstract: Purpose of review Purines have several important physiological functions as part of nucleic acids and as intracellular and extracellular signaling molecules. Purine metabolites, particularly uric acid, have been implicated in congenital and complex diseases. However, their role in complex diseases is not clear and they have both beneficial and detrimental effects on disease pathogenesis. In addition, the relationship between purines and complex diseases is affected by genetic and nutritional factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The study of pyrimidine as a cancer locator and diagnosis and treatment drug has long been of great interest to chemists, medical scientists, and biologists as 5-fluorouracil (5-FU) is an antitumor medicine widely used in the clinic . Purine is a substance in the body, mainly in the form of purine nucleotides, which play a very important role in the energy supply, metabolic regulation, and coenzyme composition . In clinical application, cytosine and thymine are mainly used to treat a variety of disease symptoms caused by a fungal infection and have high antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of pyrimidine as a cancer locator and diagnosis and treatment drug has long been of great interest to chemists, medical scientists, and biologists as 5-fluorouracil (5-FU) is an antitumor medicine widely used in the clinic . Purine is a substance in the body, mainly in the form of purine nucleotides, which play a very important role in the energy supply, metabolic regulation, and coenzyme composition . In clinical application, cytosine and thymine are mainly used to treat a variety of disease symptoms caused by a fungal infection and have high antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“… 22 Purine is a substance in the body, mainly in the form of purine nucleotides, which play a very important role in the energy supply, metabolic regulation, and coenzyme composition. 23 In clinical application, cytosine and thymine are mainly used to treat a variety of disease symptoms caused by a fungal infection and have high antibacterial activity. In this study, 7 pyrimidines and 12 purines (as shown in Table 4 ) were identified in I. hispidus samples grown on five tree species.…”
Section: Resultsmentioning
confidence: 99%
“…Purines are by-products of nucleotide metabolism, primarily in the form of purine nucleotides, which play crucial roles in the production of coenzymes, regulation of metabolism, and energy supply ( 66 , 67 ). Early purine elevation can help identify early stroke patients and predict their severity ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to fulfill the large variety of the aforementioned effects [ 17 , 18 ], purines, in particular adenine-based compounds, must be present at extracellular level where they act as signal molecules.…”
Section: Brief Outline Of the Purine System As Intercellular Signal N...mentioning
confidence: 99%